ANALYZING THE EFFECT OF EMPLOYEE COMPENSATION ON EMPLOYEE INTENTION TO STAY (STUDY IN BANK SULUTGO HEAD OFFICE) - Anter, Caroline; Lapian, S.L.H.V.J. (FEB Universitas Sam Ratulangi Manado, 2016)
Nowadays, the human resource is an important part of a company. Important for a company to pay attention to their employees by giving compensation that the employee needed and take more attention of them to make them more loyal and have a great intention to stay and work in the company. Bank SulutGo Head Office is a big finance company in Manado that give many compensations. The objective of this research is to know about the effect of compensation on employee?s intention to stay in the company by applying simple regression analysis. This research is for analyzing about the effect of employee compensation on employee intention to stay which used 100 employees? of Bank SulutGo Head Office as respondents. The result shown that compensation have effect on employee intention to stay. It can be seen from the result of R and R 2 that compensation has strong relationship with Intention to Stay. From T-test researcher got H0 is rejected and H1 is accepted and compensation influences on intention to stay. Researcher suggesting Bank SulutGo Head Office management to keep giving more diverse compensations and more attention to their employee needs. Keywords: bank sulutgo head office, compensation, intention to stay